Din Eğitimi Modelleri Çerçevesinde Türkiye’deki Din Eğitimi Üzerine Genel Bir Değerlendirme - Yıldız Kızılabdullah; Tuğrul Yürük (Dini Araştırmalar, 2015)
Generally, Grimmitt and Hull developed the differentiation of “Learning Religion, Learning about Religion and Learning from Religion” about models of religious education in the world and this differentiation had usually been used in literature of Religious Education. In this article, within the limits of this differentiation the religious education in Turkey has been studied and today, although the marks of Learning Religion and Learning about Religion approaches are seen in the curriculum of religious course, it has been determined that the approach of Learning from Religion is appropriated as the basic philosophy